Women and the Hindu right : a collection of essays - Sarkar, Tanika, 1949-; Butalia, Urvashi; Kali for Women (Organization) (New Delhi, India : Kali for Women, 1995)
With reference to India; contributed articles.
Includes bibliographical references.
Keywords: Feminism -- India; Women in politics -- India; Hinduism and politics -- India; Hindu women -- India -- Social conditions